Role of Managerial Incentives and Discretion in Hedge Fund Performance - AGARWAL, VIKAS; DANIEL, NAVEEN D.; NAIK, NARAYAN Y. (Journal of Finance, 2009)
ABSTRACT Using a comprehensive hedge fund database, we examine the role of managerial incentives and discretion in hedge fund performance. Hedge funds with greater managerial incentives, proxied by the delta of the option‐like incentive fee contracts, higher levels of managerial ownership, and the inclusion of high‐water mark provisions in the incentive contracts, are associated with superior performance. The incentive fee percentage rate by itself does not explain performance. We also find that funds with a higher degree of managerial discretion, proxied by longer lockup, notice, and redemption periods, deliver superior performance. These results are robust to using alternative performance measures and controlling for different data‐related biases.